Nanobodies As Novel Agents for Targeting Angiogenesis in Solid Cancers - Arezumand, Roghaye; Alibakhshi, Abbas; Ranjbari, Javad; Ramazani, Ali; Muyldermans, Serge (Frontiers in Immunology, 2017)
Solid cancers are dependent on angiogenesis for sustenance. The FDA approval of Bevacizumab in 2004 inspired many scientists to develop more inhibitors of angiogenesis. Although several monoclonal antibodies are being administered to successfully combat various pathologies; the complexity and large size of monoclonal antibodies seem to narrow the therapeutic applications. To improve the performance of cancer therapeutics, including those blocking tumor angiogenesis, attractive strategies such as miniaturization of the antibodies have been introduced. Nanobodies, small single domain antigen-binding antibody fragments, are becoming promising therapeutic and diagnostic proteins in oncology due to their favorable unique structural and functional properties. This review focuses on the potential and state of the art of Nanobodies to inhibit the angiogenic process for therapy and the use of labelled Nanobodies for non-invasive in vivo imaging of the tumors.